Efficacy and Safety of a Combination of Levocetirizine and Phenylephrine in the Treatment of Allergic Rhinitis and Eustachian Tube Dysfunction - Ms. Shruthi George, Mr. Lalit Pawaskar, Dr. Mayuresh Kiran, Ms. Priyanka Shah, (International Journal of Innovative Research in Medical Science, 2017)
Introduction: Allergic Rhinitis (AR) and Eustachian Tube Dysfunction (ETD) are commonly seen in adults. Treatment options for AR and ETD is directed towards multiple symptom relief. A FDC of Levocetirizine, an anti-histaminic and Phenylephrine, a nasal decongestant is popular in the treatment of Allergic Rhinitis and Eustachian Tube Dysfunction in adults. This Phase IV study judged the efficacy and safety of a combination of Levocetirizine and Phenylephrine in treatment of Allergic Rhinitis. Methodology: Of 203 registered, 174 patients completed the study. Safety assessment was made by inspecting the adverse events during trial. Efficacy assessment was made by decrease in TSS and extrapolating to four point Likert type scales. Results: Reduction in TSS was from 6.97 (baseline) to 3.90 (day 3) and 1.43 (day 5). One point reduction in Likert-type symptom scale from Moderate to Mild took just 3 days. Nearly all the patients had >50% reduction in symptom score at all visit and majority of patients had complete relief from the symptom. 23 episodes of adverse events occurred and were of mild intensity, sedation and drowsiness being dominantly seen. Conclusion: A combination of Levocetirizine and Phenylephrine is safe and effective in the treatment of Allergic Rhinitis and Eustachian Tube Dysfunction.